Canada shifts data from US. - Fine, Philip (Times Higher Education Supplement, 2006)
The article reports on the decision of Canadian universities to move their data from the U.S. to a domestic server to avoid issues associated with the U.S. Patriot Act. The move was prompted by growing fears that U.S. surveillance could target academics. Maryland-based firm RefWorks is used by academics from 650 institutions worldwide to store research information. One of the functions of the company is to store a personal database of research that can be shared with colleagues.